2017
DOI: 10.1590/1982-02752017000200007
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of life quality and prevalence of cognitive impairment, anxiety, and depressive symptoms in older adults

Abstract: Estudos de Psicologia I Campinas I 34(2) I 261-268 I abril -junho 2017

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
4
5
0
3
Order By: Relevance
“…The most cited research instruments in the articles were MMSE, GDS, sociodemographic and/or clinical instruments and WHOQOL-BREF. These data do not differ from what was observed in the current literature, since many studies use the same instruments in geriatric assessments (Anacleto, Aquino, & Rebustini, 2017;Araújo et al, 2017;Bourscheid, Mothes, & Irigaray, 2016;Rodrigues et al, 2017;Santos et al, 2017;Silveira & Portuguez, 2017).…”
Section: Discussionsupporting
confidence: 58%
“…The most cited research instruments in the articles were MMSE, GDS, sociodemographic and/or clinical instruments and WHOQOL-BREF. These data do not differ from what was observed in the current literature, since many studies use the same instruments in geriatric assessments (Anacleto, Aquino, & Rebustini, 2017;Araújo et al, 2017;Bourscheid, Mothes, & Irigaray, 2016;Rodrigues et al, 2017;Santos et al, 2017;Silveira & Portuguez, 2017).…”
Section: Discussionsupporting
confidence: 58%
“…It is believed that the elderly who have resilient reserves and characteristics, such as emotional control, optimism, maintenance of social relationships and autonomy, is able to achieve better outcomes in the management of situations that precede the symptoms of depression ( 11 ) . Other study results also showed an association between worse QOL and the presence of symptoms of depression ( 12 - 13 ) .…”
Section: Introductionmentioning
confidence: 72%
“…Demographic changes, therefore, are directly linked to the main pathologies that affect medical students given that sex is an important risk factor, especially in psychiatric disorders 15 .…”
Section: Discussionmentioning
confidence: 99%